how do we solving the x+2y-z=3, -3x+y-4z=-1, -3x+2y-2=-2 can you show me any method to make me understand

x+2y-z=3, -3x+y-4z=-1, -3x+2y-2=-2

First of all, is the last equation: -3x + 2y -z = -2 or is it -3x + 2y - 2 = -2?

for this, I would use the system of linear equations and solve it by first eliminating whatever I can using one equation with another; then substitute where I can.

1) -3x + y - 4z = -1 <------ multiply this by - 1

-3x + 2y - z = -2 (if the last term is z)

-----------------------

3x - y + 4z = 1

-3x + 2y - z = -2

----------------------

## Comments